Collaborative Governance: Tata Kelola Tempat Pembuangan Akhir (TPA) Parit Enam Kota Pangkal Pinang - Krisnawati, Krisnawati (Journal of Politics and Democracy, 2022)
This study aims to analyze the Collaborative Governance process and the factors that influence the collaborative governance between the Steam Power Plant (PLTU), the Environmental Dervice (DLH) and the Final Disposal Manager (TPA) in waste management at TPA Parit Enam Bacang Village Bukit sub-district Pangkalpinang City Diamond. In collecting data, this research uses descriptive qualitative research methods with a case study approach, namely by observation, interviews and documentation. The theory used in this research is collaborative governance theory from Anshel and Gash. The results of this study are that collaborative governance in the partnership between the Steam Power Plant (PLTU) and the Environmental Service (DLH) in waste management at TPA Parit six is considered effective. This was proven by the DLH being able to meet the work program standars proposed by the PLTU. In addition, there is good communication between the two parties, it is hoped that supervision carried out by related parties will not encounter any obstacles. The synergy between PLTU, DLH and TPA managers and the community is the key to successful waste management in Pangkalpinang City.